IMPACT OF LEARNING ORIENTATION AND SUSTAINABLE PRODUCT DEVELOPMENT THROUGH EFFICIENCY OF CAPITAL MANAGEMENT AND MARKETING MANAGEMENT OF COMMUNITY ENTERPRISES IN THE UPPER NORTEASTERN REGION - Lagkum , Nuttanun (Journal of Graduate School of Commerce-Burapha Review, 2020)
The main objectives of this study aimed to 1) investigate general characteristics of community enterprises in the upper northeastern region 2) investigate relationship and impact learning orientation and sustainable product development through efficiency of human capital management and marketing management and 3) investigate relationship and impact of capital management effectiveness relating to training on efficiency of marketing management. As for the research tool, questionnaires were distributed to the selected sample of 432 respondents who were community enterprises in upper northeastern region by using stratified random sampling. Data were collected by using a questionnaire and analyzed by using percentage, mean, standard deviation and it was then tested for validity by using the Index of Item Objective Congruence (IOC). Descriptive statistics and analysis of SEM model were employed to analyze the data. The research results were found that the majority of community enterprises were female with age between 46-55 years old, and they graduated in primary level, and their careers were farmers with income 90,000-300,000 baht/year and SEM model (X2=161.03, P=.056) and (X2= 864.53, P=.000) appropriate at level .05